Selection of Foreign Market Entry Modes and Analysis of Influating Factors in the Process of Activity’s Internationalization - Žukauskas, Pranas (Ekonomika, 1998)
The article discusses the important problem of contemporary international business - selection of entry modes to foreign markets and the main factors influating on that process. International trade and investment are a very important components of the economies for all countries. But the problem of expansion foreign markets exists for almost everyone company going international - especially for these ones from countries with transforming economies, because of lack of experience and special methodics.Author provides the classification of foreign market entry modes, describes different modes, examines the system of their crucial characteristics and designs it’s theoretical model that reflects the trends toward distribution of extent of effect of these characteristics. Considerable part of the paper is devoted to the analysis of internal and external factors influating the process of selection of entry modes to foreign markets. Author provides the complex of these factors, be especially stresses on their interdependencies, that settle the company’s relation with the market environmental situations in the process of foreseeing of activities internationalization.This study provides some contribution to management. The research helps to reinforce in executive’s mindset the importance of expanding the decision framework beyond the narrow confines of each entry decision in isolation to encompass the global strategy their firm pursues. Managers are provided with a better understanding of the importance of each variable in influencing the entry mode decision. They can better prioritize the relevant variables in evaluating their entry mode alternatives.